Human herpes virus type-6 is associated with central nervous system infections in children in Sudan - Nada A. Abdelrahim; Nahla Mohamed; Magnus Evander; Clas Ahlm; Imad M. Fadl-Elmula (African Journal of Laboratory Medicine, 2022)
Background: Human herpes virus type-6 (HHV-6) is increasingly recognised as a febrile agent in children. However, less is known in sub-Saharan African countries, including Sudan.